2015
DOI: 10.14348/molcells.2015.2254
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinases I and 2α Phosphorylate Oryza Sativa Pseudo-Response Regulator 37 (OsPRR37) in Photoperiodic Flowering in Rice

Abstract: Flowering time (or heading date) is controlled by intrinsic genetic programs in response to environmental cues, such as photoperiod and temperature. Rice, a facultative short-day (SD) plant, flowers early in SD and late in long-day (LD) conditions. Casein kinases (CKs) generally act as positive regulators in many signaling pathways in plants. In rice, Heading date 6 (Hd6) and Hd16 encode CK2α and CKI, respectively, and mainly function to delay flowering time. Additionally, the major LD-dependent floral repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 74 publications
(121 reference statements)
0
16
0
Order By: Relevance
“…Photosynthesis-related proteins were detected as previously described, with some modifications (Han et al 2012 ; Kwon et al 2015 ; Kwon et al 2017 ). Leaf tissue (10 mg) was homogenized with 100 μL of SDS-PAGE sample buffer [50 mM Tris pH 6.8, 2 mM EDTA, 10% ( w / v ) glycerol, 2% SDS, and 6% 2-mercaptoethanol] and denatured at 100 °C for 5 min, then samples were subjected to SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Photosynthesis-related proteins were detected as previously described, with some modifications (Han et al 2012 ; Kwon et al 2015 ; Kwon et al 2017 ). Leaf tissue (10 mg) was homogenized with 100 μL of SDS-PAGE sample buffer [50 mM Tris pH 6.8, 2 mM EDTA, 10% ( w / v ) glycerol, 2% SDS, and 6% 2-mercaptoethanol] and denatured at 100 °C for 5 min, then samples were subjected to SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Two other key transcriptional activators of plant growth, phytochrome interacting factor 4 (PIF4) and PIF5, regulate consumption of sugars through the circadian clock [ 34 ]. These transcription factors are activated by the morning clock proteins LHY/CCA1 and are inhibited by the evening complex (EC), Early Flowering 3 (ELF3), ELF4, and lux arrhythmo (LUX) [ 34 , 35 ]. Thus, the LHY/CCA1 complex contributes to the regulation of carbon partitioning (through b) and starch degradation (through CaK) and the EC only regulates consumption [ 13 ] ( Figure 1 ).…”
Section: Regulation Of Starch Metabolites By the Circadian Clockmentioning
confidence: 99%
“…In addition, it had been published that EL1 functions in GA signaling by demonstrating the in vitro phosphorylation of SLR1 (Dai and Xue 2010 ). EL1/CKI acts as a flowering repressor by interacting with and directly phosphorylating Ghd7 and OsPRR37; this modification delays heading date in non-inductive long-day conditions (Hori et al 2013 ; Kwon et al 2015 ). This suggests that the targets downstream of EL1/CKI act throughout various genetic and signaling pathways during rice development, such as inflorescence formation, flowering, stem elongation, and germination.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we isolated heterogeneous inbred family-near isogenic lines (HNILs) from a F 7 recombinant inbred line (RIL) heterozygous for the functional EL1 allele and the nonfunctional el1 allele (Kwon et al 2014 ). The natural missense mutation in el1 promotes flowering under non-inductive long-day conditions due to a defect in the protein kinase activity (Kwon et al 2014 , 2015 ). In this study, we found that the HNILs possessing EL1 or el1 showed different inflorescence and spikelet fertility phenotypes.…”
Section: Introductionmentioning
confidence: 99%